Impact of tropical cyclones on modeled extreme wind‐wave climate. Issue 3 (4th February 2017) - Timmermans, Ben; Stone, Dáithí; Wehner, Michael; Krishnan, Harinarayan
Abstract: The effect of forcing wind resolution on the extremes of global wind‐wave climate are investigated in numerical simulations. Forcing winds from the Community Atmosphere Model at horizontal resolutions of ∼1.0° and ∼0.25° are used to drive Wavewatch III. Differences in extreme wave height are found to manifest most strongly in tropical cyclone (TC) regions, emphasizing the need for high‐resolution forcing in those areas. Comparison with observations typically show improvement in performance with increased forcing resolution, with a strong influence in the tail of the distribution, although simulated extremes can exceed observations. A simulation for the end of the 21st century under a RCP 8.5 type emission scenario suggests further increases in extreme wave height in TC regions. Key Points: The effect of increased forcing wind resolution on simulated global wave height extremes is quantified 20‐year return levels for wave height return levels are highly dependent on resolution in tropical cyclone regions and sensitive to sampling Simulations of a future RCP 8.5 scenario suggest large increases in extreme waves in some areas